Crime and Detection in a Defective World: The Detective Fictions of Borges and Dürrenmatt - Tamara Holzapfel (Studies in 20th & 21st Century Literature, 1978)
The debt of contemporary writers to detective fiction, both in theme and technique, has been noted in recent criticism. However, studies of a comparative nature are virtually nonexistent. This article attempts to show some remarkable parallels in the approach taken by Friedrich Dürrenmatt and Jorge Luis Borges to a genre which, as yet, has not acquired recognition as literary art form. The similarities of the two authors are striking both with respect to their world view and to their transformation of the genre through poetic treatment. Detective fiction, which lends itself readily to innovation and parody, is used by these writers to meditate and comment on the reaches and limitations of human reason and on its implications for a genre that has spent itself. Proposing tentatively that its possibilities have been exhausted, Borges and Dürrenmatt discover in the process of writing a new and original form, a radically modified detective story as well as the fundamentals of a new esthetic.
Keywords: Friedrich Dürrenmatt; Jorge Luis Borges; detective fiction